Phylogeography of a tough rock survivor in European dry grasslands - Listl, Daniela (PLoS One, 2017)
Phylogeographic analyses of plants in Europe have revealed common glacial refugia and migration routes for several trees and herbs with arctic-alpine distributions. The postglacial histories of dry grassland species in central Europe have rarely been analyzed, even though the extremely species-rich habitat is threatened. Sedum album (Crassulaceae) is a common inhabitant of rocky sites in central European dry grasslands. We inferred the phylogeographic history of S. album over its distribution range in Europe. Genetic diversity within and differentiation between 34 S. album populations was examined using AFLP markers. Population isolation was indicated based on the rarity of the fragments and by isolation-by-distance effects. We sequenced the trnL-trnF region in 32 populations and used chloroplast microsatellites to analyze chloroplast haplotype distributions. Two distinct S. album lineages were detected. One lineage was comprised of populations from eastern and central parts of central Europe, and the Apennine Peninsula. A second lineage was comprised of populations from the Iberian Peninsula and western and northern parts of central Europe. Glacial refugia were identified based on the accumulation of ancient chloroplast haplotypes, high diversity of AFLP fragments within populations, and high levels of rare fragments in Liguria, Serbia, the Apennine and Iberian peninsulas. Cryptic refugia were detected in the Czech Republic and Slovakia. Isolation by distance was present all over the distribution range, and it was separately detected in southwestern and central Europe. In western Europe, where a contact zone between the two lineages can be expected, no isolation by distance was detected. Our results suggest migration routes of S. album northeastward from glacial refugia in southern Iberia, northward from the Apennine Peninsula, and northward and westward from the southeastern parts of central Europe. Therefore, central European grasslands were recently colonized by northern cryptic populations and source populations originating in the east and the Apennine Peninsula.